2022
DOI: 10.1111/nin.12508
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 as moral breakdown: Entangled ethical demands experienced by hospital‐based nurses in the early onset of the pandemic

Abstract: 2020 saw the rapid onset of a global pandemic caused by the SARS‐CoV‐2 virus. For healthcare systems worldwide, the pandemic called upon quick organization ensuring treatment and containment measures for the new virus disease. Nurses were seen as constituting a vital instrumental professional component in this study. Due to the pandemic's unpredictable and potentially dangerous nature, nurses have faced unprecedented risks and challenges. Based on interviews and free text comment from a survey, this study expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The current study has described some of the emotional burdens experienced by frontline nurses. These findings are similar to other studies reporting experiences of burden and moral distress among HCPs witnessing the suffering of patients and relatives who were separated [7,33,34]. Moral distress can occur if an individual is unable to act in accordance with their moral judgement because of external barriers [35].…”
Section: Discussionsupporting
confidence: 89%
“…The current study has described some of the emotional burdens experienced by frontline nurses. These findings are similar to other studies reporting experiences of burden and moral distress among HCPs witnessing the suffering of patients and relatives who were separated [7,33,34]. Moral distress can occur if an individual is unable to act in accordance with their moral judgement because of external barriers [35].…”
Section: Discussionsupporting
confidence: 89%
“…SNs in this study sometimes felt constrained, depending on the power dimensions between the state of politics versus public health. Other research on nurses' experiences during COVID‐19 has found similar societal, personal, and conflicting ethical demands for nurses (Mejdahl et al., 2022; Silverman et al., 2021). The themes generated through this study brought to light how pandemic case management caused situations of moral dilemmas causing moral distress in the context of the school environment and the public health role of SNs.…”
Section: Discussionmentioning
confidence: 78%
“…We then arranged our data in meaningful groups and started identifying themes. During this step, we found a strong resonance between the codes and a potential theoretical framework 28 , 29 based on the concept of institutional logics. 19 , 20 We, therefore, re-coded the material, sorted the codes into new potential themes, and combined the relevant coded extracts into the identified themes.…”
Section: Methodsmentioning
confidence: 97%